Evaluasi Kinerja Angkutan Umum Di Kota Singaraja - Triatna, Ni Nyoman; Herawati, Herawati (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
ABSTRACTTirerc is a serious problem 011 Public transportation in Singaraja city dealing with tire increasingnumber of 111otora;cle lzas declined people interest to use public transport. People feel more comfortable using 111otorcycles for tlzeir daily activities.As the conequense urban public transport seruices in Singaraja lzas not reached local road. Since the rates charged are quite e:xpensive as well. TJ1iere fore people pr fer to use public private titan transport vehicles. this condition may bring public transportation in Si11garaja get worst. Two methods are carried out to calculate the quality of public transport services first accordance witlz the standards of the Directorate General of Land Transportation Ministry of Transportation and second, utilize tlze nzetlwd of Importance Performance Analysis (IPA). Based on the results due to the standards of tire Directorate General of Land Transportation Ministry of Transportation the city transportation in Singaraja still have good performance. While the result analysis of Importance Pe1formance Analysis (IPA) showed that 15 factor indicators, three factors indecated has a good perfomiance vehicle that is hygiene, driver peiformance and the route, seven factors indicated not important perfonnance and less priority by the transport users such as the walking time to the destination, no need moving vehicle, easily get in and get out the vehicle, additional facilities (music, etc.) and travel cost. The factors are needed to be handling quite serious because it has a less peiformance and very important by respondents such as courteous service, seat comfort, tire physical conditio11 of public transport, vehicle speed and safety in vehicles.Key Words: public transport, services, Singaraja